2019
DOI: 10.3390/fishes5010001
|View full text |Cite
|
Sign up to set email alerts
|

Seabream Larval Physiology under Ocean Warming and Acidification

Abstract: The vulnerability of early fish stages represents a critical bottleneck for fish recruitment; therefore, it is essential to understand how climate change affects their physiology for more sustainable management of fisheries. Here, we investigated the effects of warming (OW; +4 °C) and acidification (OA; ΔpH = 0.5) on the heart and oxygen consumption rates, metabolic enzymatic machinery—namely citrate synthase (CS), lactate dehydrogenase (LDH), and ß-hydroxyacyl CoA dehydrogenase (HOAD), of seabream (Sparus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 68 publications
1
13
0
Order By: Relevance
“…This is the case of studies focused on establishing the potential effects of the climate change over fish species. Most studies on this issue exposed contemporary populations of fishes to global warming (higher mean water temperature and ocean acidification) that progressively will take place in the coming years [14][15][16][17][18]37], neglecting the capacity of fish species to adapt to this environmental condition through the different generations. Here, we explored the effect of a more extreme event (although shorter in time, only lasting some days) related to climate change, the heat waves, a contemporary event which frequency and intensity are predicted to be increased [1].…”
Section: Discussionmentioning
confidence: 99%
“…This is the case of studies focused on establishing the potential effects of the climate change over fish species. Most studies on this issue exposed contemporary populations of fishes to global warming (higher mean water temperature and ocean acidification) that progressively will take place in the coming years [14][15][16][17][18]37], neglecting the capacity of fish species to adapt to this environmental condition through the different generations. Here, we explored the effect of a more extreme event (although shorter in time, only lasting some days) related to climate change, the heat waves, a contemporary event which frequency and intensity are predicted to be increased [1].…”
Section: Discussionmentioning
confidence: 99%
“…Some tendencies were observed when CS/CCO and LDH/CS ratios of activities were considered but further studies are needed to confirm these results. Higher LDH/CS could indicate a transition from aerobic to anaerobic metabolism [70], while a lower CS/CCO ratio could reveal mitochondrial dysfunction [35]. Craig et al [14] observed that Cu exposure affected this ratio in the liver of the gilthead seabream (Sparus aurata) and suggested that it could, therefore, affect normal mitochondrial biogenic processes.…”
Section: Discussionmentioning
confidence: 99%
“…Ten larvae per replicate (n= 30 per treatment) were placed after hatch in sealed water-jacketed respirometry chambers, lled with seawater from the respective treatment (according to Pimentel et al 2019). Water volumes were adjusted to allow routine activity and to minimize larval stress.…”
Section: Routine Heart Ratesmentioning
confidence: 99%
“…Water volumes were adjusted to allow routine activity and to minimize larval stress. Routine heart rates measurements were taken at the end of the experiment under a stereoscope (Leica S6D, Leica Microsystems), and de ned as the number of heart beats per unit of time when larvae were not swimming (according to Pimentel et al 2019).…”
Section: Routine Heart Ratesmentioning
confidence: 99%